108k views
1 vote
Hello, the question is in the picture :)

Hello, the question is in the picture :)-example-1

1 Answer

2 votes

By cross multiplying the given equation, we have


6x=(x-2)(x+8)

By multiplying the right hand side, we get


6x=x^2+6x-16

Then, by subtracting 6x to both sides, we have


0=x^2-16

or equivalently,


x^2-16=0

Since the left hand side is a conjugate binomial, it can be expressed as


x^2-16=(x+4)(x-4)

Then, we have the equation


(x+4)(x-4)=0

Therefore, the values of x that make the equation true are x= 4 and x= -4

User Keeganwatkins
by
5.0k points